Depression among Cancer Patients: Risk Factors and Coping Mechanism - Alvi, Aaqib Shahzad; Sajid, Ibad Ullah; Ashraf, Muhammad; Tarar, Muhammad Ali; Bilal, Hira (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To gauge the prevalence of depression and; identify the potential risk factors as well as coping strategies among cancer patients. Methodology: This descriptive cross-sectional study was conducted during from March-2018 to November-2018 at Clinical Oncology Department, Institute of Nuclear Medicine and Oncology Lahore (INMOL) Lahore. The purposive sampling technique was used and interviewed 118 sampled cancer patients. Interview schedule, depression Scale and coping scales were used as instrument to collect data. Depression items, age, economic status, family support, duration of cancer, stage of cancer and coping strategies were the variables of the study. Results: The results of the study indicated that 16% respondents had low level of depression, 72% medium while 12% had high level of depression. In case of coping mechanism, majority of respondents adopted cognitive restriction, emotional expression, information seeking, self-blame, Wish Fulfilling Fantasy, and threat minimization as coping styles. All the predictor variables including age, economic status, family support, and duration of cancer were found significantly associated with depression. The results of correlation analysis indicated a negative association between depression and coping strategies. Conclusion: Considering the diverse effect of depression and repeated use of various coping strategies, comprehensive steps are needed to screening and counseling of cancer patients that will be effective for their mental wellbeing.